An Exploration of System Quality Factors Influencing University Students' Satisfaction with WeChat Official Account Applications in Xi'an City, Shaanxi Province, China - DU, Xintian; Liang, Hui; Khong-khai, Sutthikarn (วารสารร่มยูงทอง, 2026)
This study examined university students' satisfaction with WeChat Official Account applications in Xi'an City, Shaanxi Province, China, based on the system quality construct of the Information Systems Success Model. It had two objectives: to examine the levels of system quality across five dimensions (adaptability, availability, reliability, response time, and usability) and of satisfaction, and to analyse the influence of these system quality dimensions on satisfaction. Data were collected from 400 university students who had used a university WeChat Official Account, selected through proportional stratified sampling, using a five-point Likert-scale questionnaire. The data were analysed using descriptive statistics and stepwise multiple regression. The results showed that both system quality (mean = 2.21) and satisfaction (mean = 2.12) were rated at low levels. The stepwise regression model was statistically significant (F = 406.344, p < 0.001) and explained 80.3% of the variance in satisfaction (Adjusted R² = 0.803). Usability (β = 0.281), response time (β = 0.256), availability (β = 0.223), and reliability (β = 0.223) were each significantly and positively associated with satisfaction, while the adaptability dimension could not be reliably assessed, as its scale did not achieve internal consistency. These findings suggest that usability, response time, availability, and reliability are significant system quality factors associated with student satisfaction. As the four dimensions carried closely comparable weights, universities seeking to improve satisfaction should strengthen them together rather than prioritising any single one.